Residual Soluble Organics from the Activated Sludge Process - Sedivy, Milan J. (My University, 1971)
A completely-mixed batch biochemical reactor was used to study the degradation of soluble organic carbon using a mixed microbial culture. Carbon sources, representative of actual wastes were chosen from among those whose metabolism has been described in the literature, and included: a) Phenol - an aromatic hydrocarbon b) Glutamic acid - an aminoacid c) Glucose - a monosaccharide, and d) Starch - a polysaccharide. Experiments were performed to determine if a mathematical relationship could be developed between the level of residual organic carbon and operating parameters of the activated sludge process. An organic residue which could not be removed from the liquid medium even after an extended period of contact of the waste with activated sludge was monitored during the batch tests. Also, measurements of specific substrate degradation, and the total oxygen demand were analysed during the tests.
Title: Residual Soluble Organics from the Activated Sludge Process, Author: Milan J. Sedivy, Location: Thode